PEMANFAATAN TEKNOLOGI AKUAPONIK PADA STRAIN IKAN NILA (Oreochromis niloticus) YANG BERBEDA TERHADAP PERPORMA PERTUMBUHAN - Firmansyah, Taufiq; hermawan, dodi; Agung, Lukman Anugrah (Leuit (Journal of Local Food Security), 2023)
Along with the rapid pace of development, therefore one of the consequences that must be addressed is the reduction in fresh water resources, especially in urban areas and reduced cultivated land. One of the technological innovations that can be applied to integrated fish farming with crop through aquaponics system. At this time various types of tilapia developed by the fish farmer, such as tilapia BEST, Sultana and Gesit. The performance of three strains should be tested with aquaponics system so that farmers can choose the right strain and use the land and water availability are difficult. This study was aimed to evaluate the three strains of tilapia in aquaponics technology systems that support the growth and survival rates are optimal. This study applied a completely randomized experimental design comprising three strains of tilapia namely BEST, Sultana and Gesit and each in three replicates. These results indicate that the differences in the three strains of tilapia (BEST, Sultana and Gesit) did not have a significant influence on the specific growth rate, but the real impact against the survival rate and feed conversion ratio. Sultana tilapia and tilapia BEST maintained at aquaponics system gives a better effect on the survival rate and feed conversion ratio. The survival rate of tilapia Sultana of 100%0,00 and tilapia BEST amounted to 98.41%±1,37 in the feed conversion ratio of tilapia Sultana of 1.27%±0,003 and tilapia BEST of 1.29%±0,01.